Tin doping effect on crystallization of amorphous silicon obtained by vapor deposition in vacuum - Neimash, V.B.; Poroshin, V.M.; Shepeliavyi, P.Ye.; Yukhymchuk, V.O.; Melnyk, V.V.; Makara, M.A.; Kuzmich, A.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The influence of tin impurity on amorphous silicon crystallization was
investigated using the methods of Raman scattering, Auger spectroscopy at ion etching,
scanning electron microscopy and X-ray fluorescence microanalysis in thin films of
Si:Sn alloy manufactured by thermal evaporation. Formation of Si crystals of the 2 to 4-
nm size has been found in the amorphous matrix alloy formed at the temperature 300 C.
Total volume of nanocrystals correlates with the content of tin and can comprise as much
as 80% of the film. The effect of tin-induced crystallization of amorphous silicon
occurred only if there are clusters of metallic tin in the amorphous matrix. The
mechanism of tin-induced crystallization of silicon that has been proposed takes into
account the processes in eutectic layer at the interface metal tin – amorphous silicon.